Continuous positive airway pressure (CPAP) provision with a pediatric helmet for treatment of hypoxemic acute respiratory failure in dogs. Issue 1 (23rd December 2019) - Ceccherini, Gianila; Lippi, Ilaria; Citi, Simonetta; Perondi, Francesca; Pamapanini, Michela; Guidi, Grazia; Briganti, Angela
Abstract: Objective: To evaluate arterial blood gas parameters and pulmonary radiography, before and after provision of continuous positive airway pressure (CPAP) via a pediatric helmet in dogs with acute hypoxemic respiratory failure. Design: Single‐center, observational study conducted from 2016 to 2017. Setting: University teaching hospital. Animals: Seventeen dogs presenting with clinical signs compatible with respiratory failure, confirmed by arterial blood gas analyses. Interventions: For each animal arterial blood samples and thoracic radiographs were performed at arrival (T0 ). Hypoxemic dogs (PaO2  <80 mm Hg), without evidence of pneumothorax or pleural effusion, received CPAP ventilation via a pediatric Helmet for at least 1 hour. At the end of CPAP ventilation, a second arterial blood gas analysis was performed at room air (T1 ). The F‐shunt was also calculated. Measurement and Main Results: Respiratory rate, heart rate and rhythm, mean blood pressure, mucosal membrane color, and rectal temperature were recorded. Tolerance to the helmet was evaluated using a predetermined scoring system. Two dogs were excluded from the study for low tolerance to the helmet. In 15 of 17 dogs, a significant difference between T0 and T1 was noted for PaO2 (60.84 ± 3 mm Hg vs 80.2 ± 5.5 mm Hg), P(A‐a)O2 (52.4 ± 4.4 mm Hg vs 35.2 ± 6 mm Hg), PaO2 /FiO2 (289.7 ± 14.3 vs 371 ± 21), and %SO2 (91.3 vs 98.8). In 15 of 17 dogs, the helmet was well tolerated. F‐shunt significantly decreased following provision of CPAP (37%; range, 8.4–68% vs 6%; range, −5.6–64.3%). Conclusion: The use of a pediatric helmet appears to be a suitable device for delivery of CPAP in dogs with hypoxemic acute respiratory failure. The device appears to be reasonably tolerated and improved oxygenation in most dogs.